2022
DOI: 10.3390/ani12172185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Essential Oil Blends on In Vitro Apparent and Truly Degradable Dry Matter, Efficiency of Microbial Production, Total Short-Chain Fatty Acids and Greenhouse Gas Emissions of Two Dairy Cow Diets

Abstract: The current study evaluated nine essential oil blends (EOBs) for their effects on ruminal in vitro dry matter digestibility (IVDMD), efficiency of microbial production, total short-chain fatty acid concentration (SCFA), total gas, and greenhouse gas (GHG) emissions using two dietary substrates (high forage and high concentrate). The study was arranged as a 2 × 2 × 9 + 1 factorial design to evaluate the effects of the nine EOBs on the two dietary substrates at two time points (6 and 24 h). The inclusion levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 38 publications
6
25
6
Order By: Relevance
“…A significant (p < 0.001) decrease in partitioning factor (PF) in the treated samples after 48 h of in vitro batch culture fermentation could be a result of its higher gas production (187 mL) compared with the lowest gas volume (3.56 mL) noted for untreated samples at 6 h. Lower PF in the current study due to higher gas production is expected as total gas volume is one of the variables used in calculating PF. This is in contrast with [59,70] who reported higher values for both PF and microbial mass. The use of essential oil blends in [59] which is known to depress gas production could be responsible for the higher PF values.…”
Section: In Vitro Gas Production and Efficiency Of Microbial Protein ...contrasting
confidence: 99%
See 2 more Smart Citations
“…A significant (p < 0.001) decrease in partitioning factor (PF) in the treated samples after 48 h of in vitro batch culture fermentation could be a result of its higher gas production (187 mL) compared with the lowest gas volume (3.56 mL) noted for untreated samples at 6 h. Lower PF in the current study due to higher gas production is expected as total gas volume is one of the variables used in calculating PF. This is in contrast with [59,70] who reported higher values for both PF and microbial mass. The use of essential oil blends in [59] which is known to depress gas production could be responsible for the higher PF values.…”
Section: In Vitro Gas Production and Efficiency Of Microbial Protein ...contrasting
confidence: 99%
“…This is in contrast with [59,70] who reported higher values for both PF and microbial mass. The use of essential oil blends in [59] which is known to depress gas production could be responsible for the higher PF values. In [18], the authors reported that a decrease in gas production for P. ostreatus treated corn stover could be related to the proportion of lignin in the original substrate.…”
Section: In Vitro Gas Production and Efficiency Of Microbial Protein ...contrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, the lower EE content noted in the corn stover fermented for 2 wk tends to favor the activities of rumen microbes [ 41 , 42 ] as a higher EE concentration is known to have negative effect on the digestibility of DM. Thus, the 2 wk treated corn stover demonstrated a better nutrient profile in terms of DM, CP, ash and EE.…”
Section: Resultsmentioning
confidence: 99%
“…Manh et al show that eucalyptus leaf meal addition at 100 g/d for grazing animals could be an alternative feed booster: it reduces the development of rumen methane gas in cattle while preserving mineral digestion [ 117 ]. Oregano and white thyme essential oils can modulate ruminal fermentation and decrease rumen methanogenesis without affecting feed digestibility, showing promise as alternatives to ionophores for methane reduction in beef cattle [ 119 , 135 ]. Moreover, it was studied that cinnamon and cloves have a phenolic monoterpene that demonstrated antimicrobial activity against both Gram-positive and Gram-negative [ 136 ].…”
Section: Methods To Reduce Ghgmentioning
confidence: 99%